Liquid biopsy-A biomarker‐based revolutionising technique in cancer therapy - Subham Sarkar; Samraggi Chakraborty; Soubhagya Ghosh; Ekanansha Roy Chowdhury; Jenifer Rajak; Arup Kumar Mitra; Ajoy Kumer; Bikram Dhara (Wiley, 2024)
Abstract Background and Aims Cancer has grabbed the attention of scientists and medical professionals all over the world much more than any other disease. In the past few decades, the medical field has improved quite a lot but progress in the path to find a solution for cancer is very less. As the popularity of invasive technologies is diminishing in cancer treatment, scientists have come up withminimally invasive or non‐invasive alternatives, among which liquid biopsy, by far is the most suitable. Methods Liquid biopsy is used to analyse nucleic acids, subcellular components and circulating tumour cells in various biological fluids for diagnosis of cancer. It can also be used to know the efficacy of cancer drugs in a patient by analysing multiple samples. Outcomes Liquid biopsy is becoming standard of care as it allows biopsy of those samples in which solid tumour biopsies are not possible. The diversity of sampling procedures, such as collection of urine for urothelial carcinoma or bladder or prostate cancer and phlebotomy for other types of cancer, make liquid biopsy one of the best methods for diagnosis of cancer. Conclusion This review aims in discussing the several techniques used for the detection of cancer biomarkers and some clinical manifestations due to the changes in the biomarkers which are analysed by liquid biopsy.